The Role of School Leadership in Supporting the Implementation of Differentiated Instruction at SMPN 4 Talisayan - Prasetyo, Teguh; Baco, Asmar; Tunggal, Anggunan; Warman, Warman; Fitriadi, Ahmad (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to analyze the role of school leadership in supporting the implementation of differentiated instruction at SMPN 4 Talisayan. Differentiated instruction is an approach that adapts teaching strategies to students' needs, interests, and abilities to enhance learning outcomes and engagement. This research employs a qualitative approach with a case study design, involving in-depth interviews, observations, and document analysis to obtain comprehensive data. The findings indicate that the principal acts as a facilitator, innovator, and motivator in ensuring the successful implementation of differentiated instruction. Key strategies include teacher training and professional development, mentoring and classroom observation, and the provision of policies and resources that support differentiated learning. However, challenges persist, such as resistance to change, limited teacher time for lesson planning, and inadequate supporting facilities. To address these obstacles, the principal fosters a collaborative culture among teachers, provides flexibility in time management, and increases parental and community involvement in supporting student learning. Thus, transformative and adaptive school leadership plays a crucial role in creating an inclusive and responsive learning environment. This study recommends increased support from policymakers in the form of flexible policies, resource provision, and more intensive teacher training programs to ensure the sustainability of differentiated instruction in schools.